PEMBELAJARAN IPA BERBENTUK LOMBA BAGI MURID SEKOLAH DASAR DI KELURAHAN NAIONI KUPANG: - - Gertreda Latumakulita; Lodowik Landi Pote; Christiani Dewi Qeken Mariano Bulin (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Although the current situation is relatively conducive, a new problem has emerged in the form of a decrease in students' comprehension and understanding of their learning, as happened at GMIT Naioni Elementary School and Tiga Putera Elementary School. It was found that third and fourth graders had difficulty understanding Science due to limited interaction, incomplete explanations, and difficulties in reading texts. Using a focused group discussion approach with the main objective of looking at the attitudes, beliefs, and reactions of respondents more holistically, this service activity is carried out. It can be seen that this activity went well marked by the enthusiasm of the students when competing. Some students who have difficulty reading are helped by the teacher and the committee team, resulted in presenting well in front of the judges. Moreover, a conducive and competitive learning climate is created when students look at the trophy with burning ambition. In conclusion, this service activity was successful. It can be seen from the third and fourth grade students of SD GMIT Naioni and SD Tiga Putera’s enthusiasm and motivation to compete and participate in the science script reading competition as well as the understanding of science that is starting to form, by the skills of the students when telling stories of the script quickly and precisely. Keywords: Science, Competition, Naioni